2006
DOI: 10.1007/s10509-006-9272-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-Existence of Five Dimensional Perfect Fluid Cosmological Model in Lyra Manifold

Abstract: In this paper we have taken an attempt to construct a five dimensional perfect fluid cosmological model within the framework of Lyra manifold. It is found that neither perfect fluid nor dust distributions survive. Finally the exact solutions of the vacuum field equations are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Guth (1981) and Alvarez and Gavela (1983) observed that during contraction process extra dimensions produce large amount of entropy, which provides an alternative resolution to the flatness and horizon problems as compared to usual inflationary scenario. Further Freund (1982), Appelquist and Chodos (1983), RandjbarDaemi et al (1984), Rahaman et al (2002), Singh et al (2004) and Mohanty et al (2006) claimed through solutions of the field equations that there is an expansion of four dimensional space-time while fifth dimension contracts or remains constant.…”
Section: Introductionmentioning
confidence: 99%
“…Guth (1981) and Alvarez and Gavela (1983) observed that during contraction process extra dimensions produce large amount of entropy, which provides an alternative resolution to the flatness and horizon problems as compared to usual inflationary scenario. Further Freund (1982), Appelquist and Chodos (1983), RandjbarDaemi et al (1984), Rahaman et al (2002), Singh et al (2004) and Mohanty et al (2006) claimed through solutions of the field equations that there is an expansion of four dimensional space-time while fifth dimension contracts or remains constant.…”
Section: Introductionmentioning
confidence: 99%
“…Singh and Singh (1991) have given exhaustive review of cosmological models based on Lyra's geometry with time dependent and constant displacement vector. Subsequent studies in scalar tensor theory and cosmology within the framework of Lyra's geometry, have also been done by Beesham (1986Beesham ( , 1988, Reddy and Venkateshwarlu (1987), Singh (1997), Chakraborty and Ghosh (2000), Rahaman and Bera (2001), Rahaman et al (2002), Mohanty et al (2006) and Pradhan and Vishwakarma (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Various authors (Rahaman et al 2003;Reddy 2005) constructed string cosmological models in Lyra's geometry. Reddy and Rao (2000), Adhav et al (2005) and Mohanty et al (2006) showed that the higher dimensional perfect fluid cosmological models do not survive in various theories. Further, Reddy (2003), Reddy and Naidu (2006) and showed that nonexistence of cosmic strings in various alternative theories.…”
Section: Introductionmentioning
confidence: 99%